(untitled) (Revista Logos Ciencia & Tecnología, 2019)
The legal system recognizes as part of parental rights, the parents' power to moderately correct their children and the right-to-relate to them in cases of life separated from the parents. The purpose of this paper is to analyze the configuration of the rights of correction and relationship in different Latin American ordinances and compare it with Spanish, studying how the police action can be specified as an authority called to collaborate with the parents, as well as outlining the police action before the breaches of the relationship regime with minors. For this, the comparative method between laws will be used. It is concluded that the regulation of the right of correction varies by country, as does the breach of the relationship regime, which some countries consider crime and others direct to the civil order.